Spiritual Leadership and Its Impact on Organizational Performance - Kumar, Rakesh (Journal of Commerce and Trade, 2017)
he purpose of this paper is to review the concept of spiritual leadership and its relationship with Organizational performance. Spiritual leadership consists of components such as vision, altruistic love, faith and Organizational Commitment. All organizations have potential for growth and success. The key is effective leadership. We have multiple bookstore shelves overflow with leadership theories. Most leadership promotes ideas based on scripture and does not imply the role of god in attaining spirituality. Spiritual leaders who simply follow secular methods and their experience to get success but will be unable to attain true spiritual leadership. People follow spiritual leaders who understand god agenda and who know how to move them on to it. In this paper, we have made an attempt to describe what spiritual leadership is and how it affects the organisanational performance. JEL Classification : D 23, M 10, M 11.